Effects of a liquefied petroleum gas stove and fuel intervention on head circumference and length at birth: A multi-country household air pollution intervention network (HAPIN) trial - Hina Raheel; Sheela Sinharoy; Anaité Diaz-Artiga; Sarada S. Garg; Ajay Pillarisetti; Kalpana Balakrishnan; Marilu Chiang; Amy Lovvorn; Miles Kirby; Usha Ramakrishnan; Shirin Jabbarzadeh; Alexie Mukeshimana; et al. (Environment International)
Background: Air pollution may impair child growth and cognitive development, with potential markers including birth length and head circumference. Methods: The Household Air Pollution Intervention Network (HAPIN) trial was an open label multi-country-randomized controlled trial, with 3200 pregnant women aged 18–34 years (9–19 weeks of gestation) randomly assigned in a 1:1 ratio to receive liquefied petroleum gas (LPG) stove intervention compared to women continuing to cook with solid fuels for 18 months. Particulate matter ≤ 2.5 μm (PM2.5), black carbon (BC) and carbon monoxide (CO) 24-hour personal exposures were measured three times during pregnancy. Head circumference and length were measured < 24 h of birth. We conducted intention-to-treat and exposure–response analyses to determine the intervention effects and associations between household air pollution (HAP) exposure during pregnancy and head circumference, head circumference-for-gestational age Z-score, length, and length-for-gestational age Z-scores at birth. ClinicalTrials.gov. Results: Between May 2018, and Feb 2020, 3200 pregnant women were randomly assigned to intervention (n = 1593) and control groups (n = 1607) with 3060 births included in the analysis. There was a 71.9 % reduction in PM2.5 in the intervention group with similar reductions for BC and CO. Intention-to-treat analysis showed that the intervention did not affect head circumference (β = -0.01 cm, 95 %CI −0.11, 0.09), head circumference-for-gestational age Z-score (β = -0.01, 95 %CI −0.08, 0.07), or birth length (β = 0.14 cm, 95 %CI −0.01, 0.29) but did increase birth length-for-gestational age Z-score (β = 0.09, 95 %CI 0.01, 0.16). After covariate adjustment, exposure–response analysis revealed that each log-unit increase in BC was associated with a decrease in birth length-for-gestational age Z-score (β = -0.07, 95 %CI −0.13, −0.005). There was no evidence of hypothesized associations with PM2.5 or CO. Conclusion: An LPG intervention reduced HAP exposure during pregnancy but had minor effects on birth length-for-gestational age Z-score. Birth length-for-gestational age was only associated with BC.Clinical Trial Registration: The study has been registered with ClinicalTrials.gov (Identifier NCT02944682).